The effect of simulated nitrogen deposition on soil chemical properties in maple plantation stand - Mehrcedeh Tafazoli; Hamid Jalilvand; Seyyed Mohammad Hojjati; Norbert Lamersdorf (علوم محیطی)
Introduction: The amount of nitrogen compounds released into the atmosphere has increased, and is higher in industrial areas due to the increasing usage of fossil fuels and chemical fertilizers (Gruber and Galloway, 2008). Nitrogen deposition is one the consequences of increasing atmospheric nitrogen compounds. Nitrogen deposition refers to a process that nitrogen compounds in the atmosphere deposit on a solid surface (Cornell et al., 2003). Due to the lack of information about the effects of nitrogen deposition on forest soil properties, the aim of this study was to investigate the effects of simulated nitrogen deposition on soil chemical properties in a maple plantation located at the educational and research forest of Faculty of Natural Resources (Sari). Material and methods: Twelve plots of 20 m × 10 m were established in the study plantation stand. Four nitrogen treatments were considered including zero (control), 50 (low), 100 (medium) and 150 (high) kg N ha−1 year−1. Nitrogen in the form of NH4NO3 solution was manually sprayed onto the plots monthly during one year. Three soil samples were taken seasonally at a depth of 0-10 cm in each plot using a coring method and were transported to the laboratory (Xingren et al., 2017). In the laboratory, the physical properties including water content and soil texture were measured by a weighing and hydrometer method, respectively. Chemical properties of soil including pH and EC were measured by potentiometric and electrical conductivity methods, respectively (Soil to water ratio 1:2.5). Soil organic carbon, total nitrogen, phosphorus and potassium were measured using the Walkley and Black method, Kjeltec System Instrument, Olsen P extracting solution and extracted using ammonium acetate, respectively. Results and discussion: The results showed that the nitrogen deposition had significantly decreased the pH and EC. At the end of the study period, the amount of nitrogen in medium (0.47%± 0.010) and high (0.59%± 0.013) treatments was significantly higher than the control (0.36%± 0.006). The amount of phosphorus in medium (15.95± 0.39 mg kg-1) and high (14.95± 0.43 mgkg-1) treatments was significantly lower than the control (24.97± 1.05 mgkg-1). In addition, nitrogen deposition had caused a significant reduction in soil potassium. The amounts of ammonium (low: 6.04, medium: 7.23 and high: 8.53) and nitrate (low: 7.21, medium: 9.95 and high: 20.51) were significantly higher than in the control treatment (ammonium: 4.93 nitrate: 5.06). The reason for reduced soil pH and EC can be the leaching of base cations followed by leaching of nitrate and an increased ammonium concentration in the soil. The reason for increased nitrate can be its addition as well as the production of nitrate in the presence of ammonium. In general, results showed that the nitrogen deposition treatments had destructive effects on soil chemical properties that decreased pH and EC, potassium and phosphorus and increased the total nitrogen, organic Carbon, ammonium and nitrate in the soil. Conclusion: Increased nitrogen at the early stages may be partly responsible for tree growth but, with the passage of time and the saturation of nitrogen in the soil and the occurrence of nitrate leaching as well as loss of soil fertility, conditions for the growth of plants would become unsuitable. Due to a lack of data on the effects of nitrogen deposition on soil properties, extensive studies about its effects on the soil chemical and biological properties, such as soil microbial and enzyme activities as well as soil respiration, is suggested.